Different Kinds of Discrete Breathers in Three Types of One-Dimensional Models - 吕彬彬 田强 (Communications in theoretical physics, 2010)
The dynamics of different kinds of discrete breathers in three types of one-dimensionai monatomic chains with on-site and inter-site potentiais are investigated. The existence and evolution of symmetric breather, antisymmetric breather, and multibreather in one-dimensionai models are proved by using rotating wave approximation, local anharmonic approximation, and the numerical method. The linear stability of these breathers is investigated by using Lyapunov stable anaiysis. The localization and stability of breathers in three types of models correlate closely to the system nonlinear parameter β.